(untitled) (Journal of Informatics Education and Research, 2025)
This research paper aims to provide a comprehensive overview of health education in the school environment, which is considered an awareness strategy to reduce risk behaviors among adolescent students, based on theoretical heritage and previous studies. The descriptive-analytical method was adopted, as this topic is one of the highly important issues that should not be overlooked, given the reality observed in educational institutions, especially at the middle and secondary levels, where certain risk behaviors are increasingly prevalent. These behaviors primarily affect adolescents’ general health and, secondarily, their academic performance. Therefore, it is essential to activate health education in the school environment as an indispensable tool for fostering health awareness among adolescents, enabling them to protect themselves from various problems that affect their physical and psychological health, as well as their social and academic lives.